STUDI PERILAKU SAMBUNGAN KOLOM-KOLOM BETON PRACETAK AKIBAT BEBAN TORSI - Hardianta (NIM 25099118), Surya
Abstract : The research is purposed to study the behavior of column-column conection that is given torsion loading. The columns were loaded under monotonic loading using a quasi-static reserve loading given by an actuator located at 1000 mm measured from the center of section area of column. The specimens were fixed fixed condition. The specimens were used in two kinds, that were : monolithic column and pre-cast column. The connection on pre-cast concrete used a steel plate at middle span of column and the elements were connected with high strength bolts. The column assumption is short column where stability failure not occurred. The compressive strength of concrete was 30 MPa and the yield strength of steel was 270 MPa The testing result were torsion moment-angle of twist relationship, crack pattern , deformation and stiffness. The column monolithic had stiffness better than pre-cast\'s, and there were connection phenomenon occurred on pre-cast specimens. The testing of specimens compared with the theory analysis.